Increased Total Serum Immunoglobulin E Is Likely to Cause Complications of Mycoplasma pneumoniae Pneumonia in Children - Zhou, Lili; Li, Yuan; Xu, Zhufei; Peng, Xuyun; Gong, Xiaoyan; Yang, Lin (Frontiers in Cellular and Infection Microbiology, 2021)
Objective To investigate the correlation between serum immunoglobulin E (IgE) levels and the complications in children with Mycoplasma pneumoniae pneumonia (MPP). Methods A retrospective study of MPP patients hospitalized from May 2019 to July 2021 was performed. We analyzed the clinical manifestations, complications, laboratory findings, and treatments. Results A total of 275 patients who met the inclusion criteria were enrolled in the study. We divided patients into two groups based on whether there were complications. Complications occurred in 147 patients, of which pulmonary complications were more common than extrapulmonary complications. The IgE level in the complication group was higher than that in the non-complication group with p = 0.041. Patients with complications of necrotizing pneumonitis, pneumothorax, skin rash, or bronchiolitis obliterans had higher IgE levels. There was no statistically significant difference in IgE levels between pulmonary complications and extrapulmonary complications. The older the age, the greater the probability of complications (p = 0.001). The group with complications was more likely to have chest pain (p = 0.000), while the group without complications was more likely to have wheezing (p = 0.017). The use of bronchoscopy and glucocorticoids was higher in the complication group than in the non-complication group (p = 0.000). Conclusions MPP patients with higher IgE levels had more severe clinical symptoms and complications. We speculated that IgE might be a biomarker for complications after MP infection.